Higher Maximum Temperature Increases the Frequency of Water Drinking in Mountain Gorillas (Gorilla beringei beringei) - Wright, Edward; Eckardt, Winnie; Refisch, Johannes; Bitariho, Robert; Grueter, Cyril C.; Ganas-Swaray, Jessica; Stoinski, Tara S.; Robbins, Martha M. (Frontiers in Conservation Science, 2022)
Water plays a vital role in many aspects of sustaining life, including thermoregulation. Given that increasing temperatures and more extreme weather events due to climate change are predicted to influence water availability, understanding how species obtain and use water is critical. This is especially true for endangered species in small isolated populations which are vulnerable to drought and the risk of extinction. We examined the relationship between the frequency of water drinking and maximum temperature and rainfall in 21 groups of wild gorillas from the two mountain gorilla populations (Bwindi and Virunga), between 2010 and 2020. In both populations, we found that the frequency of water drinking significantly increased at higher maximum temperatures than cooler ones, but we found no consistent relationship between water drinking and rainfall. We also found that Virunga gorillas relied more on foods with higher water content than Bwindi gorillas, which in part likely explains why they drink water much less frequently. These findings highlight that even in rainforest mammals that gain most of their water requirements from food, access to free-standing water may be important because it likely facilitates evaporative cooling in response to thermoregulatory stress. These results have important implications for conservation and behaviour of mountain gorillas in the face of continued increases in temperature and frequency of extreme weather events associated with climate change.